Alternatives in improving ground handling services - Sabar, Rohafiz; Gan, Ah Mey; Yap, Wei Huan; Farhana, Zarul (2012)
This study examines the alternatives of improving ground handling services, so that the efficiency and effectiveness of ground handling services could be increased.Secondary Data such as journal and online information are collected to aid in the study.By using descriptive analysis, the relationship between independent and dependent variable were identified.The research goal is to identify and suggest several alternatives to airline in improving their ground handling services.